IMPLEMENTASI REKAM MEDIS ELEKTRONIK PADA UNIT RAWAT JALAN DI RSUD X BEKASI - Situmorang, Budi Asih; Aziz, Abdul; Subardi, Arda Yunita; Dwinuarisha, Eggie (Jurnal Penelitian Kesmasy, 2024)
Electronic medical records (EMRs) represent a significant technological transformation in Indonesia's national health system, but they still pose challenges. According to Minister of Health Regulation No. 24 of 2022, all health service facilities in Indonesia are mandated to implement EMRs. However, the adoption of EMRs across the country's healthcare facilities has not been uniform. RSUD X has been preparing for the digitization of health services since 2018 by using SIMRS Khanza, but after four years, it has yet to fully implement EMRs. In October 2022, RSUD X transitioned to a new system, SIMRS BJB Hope, and began rolling out EMRs for outpatient services in August 2023. After 10 months of implementation, this initiative was expanded to include inpatient services. The initial results show an improvement in performance indicators for outpatient services, with faster provision of medical record documents in 2023 compared to 2022. However, these improvements still fall short of the Minimum Service Standards outlined in Minister of Health Regulation No. 43 of 2016, indicating ongoing challenges in the effective implementation of EMRs in hospital services.